2022
DOI: 10.1093/bjs/znac217
|View full text |Cite
|
Sign up to set email alerts
|

Axillary surgery after neoadjuvant therapy in initially node-positive breast cancer: international EUBREAST survey

Abstract: Background There is no consensus on axillary management after neoadjuvant therapy (NAT) in patients with clinically node-positive (cN+) breast cancer. To investigate current clinical practice, an international survey was conducted among breast surgeons and radiation oncologists. The aim of the first part of the survey was to provide a snapshot of international discrepancies regarding axillary surgery in this context. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…For this reason, axillary involvement is usually considered an indication to NAC in most T1-T2 operable BC presenting nodal involvement at diagnosis. Unfortunately, when cN + does not convert to cN0 after NAC, ALND is recommended 14 . Therefore, the identi cation of pre-NAC markers that are predictive of axillary response might be useful in selecting those patients who may bene t from chemotherapy in terms of lymph node downstaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, axillary involvement is usually considered an indication to NAC in most T1-T2 operable BC presenting nodal involvement at diagnosis. Unfortunately, when cN + does not convert to cN0 after NAC, ALND is recommended 14 . Therefore, the identi cation of pre-NAC markers that are predictive of axillary response might be useful in selecting those patients who may bene t from chemotherapy in terms of lymph node downstaging.…”
Section: Discussionmentioning
confidence: 99%
“…A large meta-analysis on 13 studies including over 1900 women documented a false negative rate exceeding 10% for SLNB technique in this setting 13 . A recent international EUBREAST survey among 349 international breast units demonstrated that standard ALND or target ALND are still the preferred approach in these patients 14 . In 2021, our group developed and validated a post-NAC predictive nomogram to select cN + BC patients with a low risk of residual axillary disease after NAC in whom axillary surgery could be minimized 15 .…”
Section: Trial Registrationmentioning
confidence: 99%
“…Recently, the results of the international EUBREAST survey on surgical management of the axilla were reported [66]. 349 physicians from 45 countries completed a detailed online questionnaire on their approach to specific clinical scenarios.…”
Section: Scenario 5 Cn + Before Pstmentioning
confidence: 99%
“…Nevertheless, all authors justifiably warn that the above-mentioned data do not comprise level 1 evidence, and that the ongoing RCTs will have to be awaited before firm conclusions can be drawn. From a recent survey by the European Breast Cancer Research Association of Surgical Trialists (EUBREAST) it is clear that this lack of level 1 evidence leads to a wide heterogeneity in surgical approaches to the axilla after PST [ 66 ]. To overcome the current problem that in many (surgical) studies important radiation details are lacking, the Breast Cancer subcommittee of ESTRO guidelines is currently developing Quality Assurance guidelines regarding the reporting of radiation details in trials.…”
Section: Further Considerationsmentioning
confidence: 99%